PERCEPTION ABOUT ICDS SERVICES IN A RURAL POPULATION OF LUCKNOW, UTTAR PRADESH - Pandey, Vandana; Swatantra, K; Srivastava, Vinod Kumar (Indian Journal of Community Health, 2013)
Objective: To assess the perception of mother/fathers about the Anganwadicentres in a rural block of Lucknow district. Study design:Cross-sectional study.Study site: Kakori Block of Lucknow district, UP.Study subjects:Mothers/fathers whose children were attending the Anganwadicentre to receive the ICDS scheme.Results: A total of 453 mothers/fathers were interviewed. Majority (86.8%) belonged to Hindu community and scheduled caste (62.8%).More than half(63.8%) of the respondents viewed that their children received cooked food item as one full glass measure (80 grams) per day. About half (53.9%) of the respondents viewed that their children consumed food items at the AWCs itself, while 24.2% viewed that children brought it partially at home. However, 21.9% of them viewed that they brought all the food items at home whatever they received. About one third (33.8%) of the respondents perceived that the purpose of enrolment at AWCs of their children was learning.Majority (81.9%) of the respondents viewed that there were the benefits of AWC in the village.Conclusions: The ICDS scheme may be very attractive but beneficiaries do not realize its importance. Proper and sufficient nutritional supplementation provided to beneficiaries may help children towards leading a nutritionally sound and healthy life and combat malnutrition.